Tren, Tantangan, dan Perspektif dalam Sistem Logistik pada Masa dan Pasca (New Normal) Pandemik Covid-19 di Indonesia - Nova Indah Saragih; Verani Hartati; Muchammad Fauzi (Jurnal Rekayasa Sistem Industri, 2020)
This paper discusses trends, challenges, and perspectives in logistics system of Indonesia during and post (new normal) of Covid-19 pandemic. PSBB (Large-Scale Social Restriction) caused a number of supply chains to be cut and made railroad transportation activities decreased. On the other hand, WFH (Work From Home) caused sector of e-Commerce to grow during the pandemic. Challenges in logistics system of Indonesia during the pandemic are changes in distribution patterns, changes in handling processes, changes in facilities and equipment, changes in business processes, and changes in networks. Adaptations in logistics system during the pandemic are using ICT (information and communication technology) such as TMS (Transportation Management System) and EDI (Electronic Data Interchange) and considering health. WMS (Warehouse Management System) still has a great opportunity to be utilized. The adaptations raise a new discipline in Industrial Engineering, namely logistics hygienic. The use of various ICTs in logistics system together with implementation of health protocols are expected to be a solution for logistics system in Indonesia, especially for the new normal of Covid-19 pandemic.